2018
DOI: 10.1093/molbev/msy130
|View full text |Cite
|
Sign up to set email alerts
|

Population Genomics Provide Insights into the Evolution and Adaptation of the Eastern Honey Bee (Apis cerana)

Abstract: The mechanisms by which organisms adapt to variable environments are a fundamental question in evolutionary biology and are important to protect important species in response to a changing climate. An interesting candidate to study this question is the honey bee Apis cerana, a keystone pollinator with a wide distribution throughout a large variety of climates, that exhibits rapid dispersal. Here, we resequenced the genome of 180 A. cerana individuals from 18 populations throughout China. Using a population gen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
97
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 73 publications
(102 citation statements)
references
References 72 publications
5
97
0
Order By: Relevance
“…We conducted a kinship assessment for each population using the program plink (Purcell et al, ) with the “‐‐genome” flag. As this calculation is not LD‐sensitive, we did LD‐based pruning using the same parameters as Chen et al () (–indep 50 5 1.1). We assessed population genetic structure across all populations using two different clustering programs, snmf (Frichot, Mathieu, Trouillon, Bouchard, & François, ) and admixture v 1.3.0 (Alexander, Novembre, & Lange, ) in addition to a principal component analysis (PCA) with the function “glPca” from the adegenet R package (Jombart, ).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…We conducted a kinship assessment for each population using the program plink (Purcell et al, ) with the “‐‐genome” flag. As this calculation is not LD‐sensitive, we did LD‐based pruning using the same parameters as Chen et al () (–indep 50 5 1.1). We assessed population genetic structure across all populations using two different clustering programs, snmf (Frichot, Mathieu, Trouillon, Bouchard, & François, ) and admixture v 1.3.0 (Alexander, Novembre, & Lange, ) in addition to a principal component analysis (PCA) with the function “glPca” from the adegenet R package (Jombart, ).…”
Section: Methodsmentioning
confidence: 99%
“…Physiological and behavioural differences may also be involved in this local adaptation. In a recent study based on WGS, A. cerana populations sampled across China were found to have limited levels of population structure, with the highest levels of genome differentiation and lower genetic diversity observed in isolated mountain or island populations (Chen et al, ), indicating a greater degree of reproductive isolation. However, the molecular basis of the phenotypic differences exhibited by highland populations is unknown.…”
Section: Introductionmentioning
confidence: 99%
“…And thirdly, the gut microbiota of A. mellifera harbored a much larger repertoire of enzymes related to polysaccharide breakdown. Thus, in the time since their last common ancestor, approximately 6 million years ago [20, 23], the gut bacterial communities of A. mellifera and A. cerana seem to have undergone substantial changes in composition, genomic diversity, and functionality, with likely consequences for the interaction with their hosts.…”
Section: Discussionmentioning
confidence: 99%
“…In the current study, we perform a comparative metagenomic analysis of the gut microbiota of two closely related species of honey bees, Apis mellifera and Apis cerana . Based on molecular data, their last common ancestor has been dated to approximately 6 million years ago [2023], and previous 16S rRNA-based studies have shown that they harbor largely overlapping gut microbiota phylotypes (>97% 16S rRNA identity) [13]. With the exception of A. mellifera , all extant species of honey bees (genus Apis ) are confined to Asia, pointing towards an Asian origin of the Apis genus [21].…”
Section: Introductionmentioning
confidence: 99%
“…These A. cerana populations differ in their nesting behaviour, such as the number of combs or even in their body size 86 . In China alone, A. cerana populations were shown to be as genetically divergent for more than 300,000 to 500,000 years (earlier than the recognized level of subspecies for A. mellifera) 112 . In addition to genetic differences between the hosts, 585 the climactic environments across Asia are highly variable and could result in local adaptation, though, as mentioned earlier, this did not prevent range expansions after switching hosts (Figure 1) 79,81 and may remain undetected.…”
mentioning
confidence: 99%